Creative teaching strategies that affect meaningful learning in virtual environments of Language and Literature - Moreira, Howard (2022)
The objective of this research was to analyze the use of creative didactic strategies and their impact on meaningful learning in virtual environments of Language and Literature of the students of the Third Baccalaureate of the Educational Unit "Dr. Carlos Romo Davila”; the work was carried out under a mixed approach, being this exploratory and bibliographical. For the factual study, surveys and a checklist were applied, for its development, the use of creative didactic strategies for virtual environments was identified through the survey applied to 11 teachers and 40 students. It was possible to detect that the strategies were not applied, becoming a factor so that the students do not receive the knowledge according to the need of the educational system, therefore; We proceeded to theoretically base meaningful learning in virtual environments, announcing that taking a class that generates significant learning in our students, it is necessary to apply creative, individual or collaborative didactic strategies or tools that help strengthen the teaching process, affecting the learning of students.